Universalizing health care in Brazil: Opportunities and challenges - Ana Luiza d' Ávila Viana; Hudson Pacífico da Silva; Ilcheong Yi (United Nations Research Institute for Social Development (UNRISD), 2015)
In 1988, the Brazilian Constitution established the Unified Health System (Sistema Único de Saúde, or SUS), based on universal access to health services, with health defined as a citizens right, and access to health services as an obligation of the state. Since then, Brazil has adopted a policy regime that combines both neoliberal policies - associated with those prescribed by the Washington Consensus or Bretton Woods Institutions - and more interventionist policies associated with neo-developmentalist thinking. The macroeconomic and social performance of this hybrid policy regime has been positive, insofar as the average household per capita income increased, and poverty and social inequality significantly declined. In the health sector, the capacity of the system with regard to health facilities and human resources has been expanded, while regional disparities in access to health services have been reduced. Access to primary health care has also been significantly expanded and health outcomes, such as life expectancy and infant mortality, have improved significantly. What steps did Brazil take to achieve universal health coverage, leading to substantial progress in economic and social development? Which institutions and actors have driven the universalization of health care within Brazils hybrid policy regime? This paper examines these questions within the following components of health system development: (i) the regionalization and expansion of the public health care system; (ii) stable and sufficient funding to ensure the principle of universality within the SUS; and (iii) the regulation of health science, technology and innovative procedures, and public-private relations. These components highlight the difficulties involved in moving towards universal social policies in a context of regional inequality, chronic underfunding and the great technological vulnerability of the health care system. The paper argues that the involvement of the state as strategic agent in inducing development in Brazil opens a window of opportunity to create a virtuous complementarity between health and development. However, the strength of this complementarity depends on the capacity of the government to propose and implement public policies in partnership with other actors in society, such as private companies and social movements. It also depends on whether the government has a long-term and integrated perspective which links the health sector to the countrys long-term socioeconomic development.
Keywords: 330